2023
DOI: 10.1017/jfm.2023.3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic instabilities of two successive slow/fast interfaces induced by a weak shock

Abstract: Shock-induced instability developments of two successive interfaces have attracted much attention, but remain a difficult problem to solve. The feedthrough and reverberating waves between two successive interfaces significantly influence the hydrodynamic instabilities of the two interfaces. The evolutions of two successive slow/fast interfaces driven by a weak shock wave are examined experimentally and numerically. First, a general one-dimensional theory is established to describe the movements of the two inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…Due to the very short durations of the waves interacting with the interfaces, the Dirac -function is always used to model the shock impacting the gas layer (Jacobs et al. 1995; Liang & Luo 2023 a ). Therefore, the accelerations and can be expressed as where , and have been defined in (3.1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the very short durations of the waves interacting with the interfaces, the Dirac -function is always used to model the shock impacting the gas layer (Jacobs et al. 1995; Liang & Luo 2023 a ). Therefore, the accelerations and can be expressed as where , and have been defined in (3.1).…”
Section: Resultsmentioning
confidence: 99%
“…For the second interface, the jump velocities induced by the transmitted shock (TS 1 ) and the compression waves (CW) are u 2 and u C , respectively. Due to the very short durations of the waves interacting with the interfaces, the Dirac δ-function is always used to model the shock impacting the gas layer (Jacobs et al 1995;Liang & Luo 2023a). Therefore, the accelerations g 1 and g 2 can be expressed as…”
Section: Linear Growth Of Amplitudementioning
confidence: 99%
See 1 more Smart Citation
“…2020 b ; Liang et al. 2020; Liang 2022 b ; Liang & Luo 2023). A comprehensive review of the numerical scheme and its extensive applications was recently reported by Jiang, Wen & Zhang (2020).…”
Section: Experimental and Numerical Methodsmentioning
confidence: 99%
“…The contact discontinuity restoring Harten-Lax-van Leer contact Riemann solver (Toro, Spruce & Speares 1994) is used to determine the numerical fluxes between the conservation elements. The use of this scheme in capturing shocks and details of complex flow structures for the RM instability issues and shock-droplet interactions have been well validated Guan et al 2018;Fan et al 2019;Zhai et al 2017Zhai et al , 2019bZhou et al 2020b;Liang et al 2020;Liang 2022b;Liang & Luo 2023). A comprehensive review of the numerical scheme and its extensive applications was recently reported by Jiang, Wen & Zhang (2020).…”
Section: Numerical Schemementioning
confidence: 94%